On the Reflexive KENDİ in Turkish Sign Language - Kayabaşı, Demet; Abner, Natasha (Frontiers in Psychology, 2022)
Linguistic analysis is improved when it includes language beyond the spoken modality. This paper uses sign language data to explore and advance cross-linguistic typologies of reflexives, constructions expressing that co-arguments of a predicate are also co-referent. In doing so, we also demonstrate that the lexical item KENDI in Turkish Sign Language (TİD) can function as a traditional reflexive, in addition to its previously documented emphatic functions. We further show that KENDI is a DP-type reflexive, which helps to explain the emphatic usages of KENDI that have been the focus of previous research. We end by outlining a plan for future research that can further probe and unify the superficially distinct functions of KENDI and the typology of anaphoricity across modalities. Data for the present research comes from recently conducted fieldwork interviews with two signers of the İstanbul dialect of TİD, both of whom have been exposed to TİD since birth.